PHILOSOPHICAL ANTHROPOLOGY AS AN UNFINISHED PROJECT BY RENÉ DESCARTES (Review of the Monograph by A. M. Malivskyi "Unknown Descartes: Anthropological Dimension in Philosophy") - Zahriichuk, Ivan D. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2020)
Review of the monograph by A. M. Malivskyi “Unknown Descartes: Anthropological Dimension in Philosophy”.